Towards capturing meaningful outcomes for people with dementia in psychosocial intervention research: A pan‐European consultation. (19th June 2018) - Øksnebjerg, Laila; Diaz‐Ponce, Ana; Gove, Dianne; Moniz‐Cook, Esme; Mountain, Gail; Chattat, Rabih; Woods, Bob
Abstract: Background: People with dementia are often marginalized and excluded from influence, also in relation to dementia research. There is, however, a growing requirement for inclusion through Patient and Public Involvement (PPI), but there is still limited knowledge on how researchers can fully benefit from the involvement of people with dementia in the development and testing of psychosocial interventions. This paper describes the results of a pan‐European consultation with people with dementia, synthesizing their views on outcomes of psychosocial interventions. Objective: To involve people with dementia in establishing what are meaningful outcomes when participating in psychosocial interventions. Setting and participants: Consultations took place at four divergent sites across Europe, involving twenty‐five people with dementia from nine European countries. Methods: The methods used for the consultation were developed through an iterative process involving people with dementia. Data from the consultation were analysed from a thematic analysis approach. Results: The results suggested that people with dementia wish to participate in interventions that enhance their well‐being, confidence, health, social participation and human rights. This highlights a need for improvements in psychosocial research to capture these outcomes. Discussion and conclusions: Involving people with dementia in discussions of psychosocial interventions has enhanced our understanding about meaningful outcome measures in research and methods of data collection. This study suggests that new outcome measures in psychosocial research are needed where concepts of positive psychology and social health can guide innovation and outcome measurement.